Distinct Roles of Non-Overlapping Surface Regions of the Coiled-Coil Domain in the Potato Immune Receptor Rx1. Issue 3 (7th September 2018) - Slootweg, Erik J.; Spiridon, Laurentiu N.; Martin, Eliza C.; Tameling, Wladimir I.L.; Townsend, Philip D.; Pomp, Rikus; Roosien, Jan; Drawska, Olga; Sukarta, Octavina C.A.; Schots, Arjen; Borst, Jan Willem; Joosten, Matthieu H.A.J.; et al.
Abstract : Mutation of the coiled-coil domain of the intracellular immune receptor Rx1 led to distinct cell death and resistance phenotypes and revealed regions of Rx1 required for interactions between Rx1 and the co-factor RanGAP2. Abstract: The intracellular immune receptor Rx1 of potato ( Solanum tuberosum ), which confers effector-triggered immunity to Potato virus X, consists of a central nucleotide-binding domain (NB-ARC) flanked by a carboxyl-terminal leucine-rich repeat (LRR) domain and an amino-terminal coiled-coil (CC) domain. Rx1 activity is strictly regulated by interdomain interactions between the NB-ARC and LRR, but the contribution of the CC domain in regulating Rx1 activity or immune signaling is not fully understood. Therefore, we used a structure-informed approach to investigate the role of the CC domain in Rx1 functionality. Targeted mutagenesis of CC surface residues revealed separate regions required for the intramolecular and intermolecular interaction of the CC with the NB-ARC-LRR and the cofactor Ran GTPase-activating protein2 (RanGAP2), respectively. None of the mutant Rx1 proteins was constitutively active, indicating that the CC does not contribute to the autoinhibition of Rx1 activity. Instead, the CC domain acted as a modulator of downstream responses involved in effector-triggered immunity. Systematic disruption of the hydrophobic interface between the four helices of the CC enabled the uncoupling of cell death and disease resistance responses. Moreover, a strong dominant negative effect on Rx1-mediated resistance and cell death was observed upon coexpression of the CC alone with full-length Rx1 protein, which depended on the RanGAP2-binding surface of the CC. Surprisingly, coexpression of the N-terminal half of the CC enhanced Rx1-mediated resistance, which further indicated that the CC functions as a scaffold for downstream components involved in the modulation of disease resistance or cell death signaling.